Rational Suicide, Euthanasia, and the Very Old: Two Case Reports - Anne Pamela Frances Wand; Carmelle Peisah; Brian Draper; Carolyn Jones; Henry Brodaty (Case Reports in Psychiatry)
Suicide amongst the very old is an important public health issue. Little is known about why older people may express a wish to die or request euthanasia and how such thoughts may intersect with suicide attempts. Palliative care models promote best care as holistic and relieving suffering without hastening death in severely ill patients; but what of those old people who are tired of living and may have chronic symptoms, disability, and reduced quality of life? Two cases of older people who attempted suicide but expressed a preference for euthanasia were it legal are presented in order to illustrate the complexity underlying such requests. The absence of a mood or anxiety disorder underpinning their wishes to die further emphasises the importance of understanding the individual’s narrative and the role of a formulation in guiding broad biopsychosocial approaches to management.